Advanced radiation sources and applications Proceedings of the NATO Advanced Research Workshop, held in Nor-Hamberd, Yerevan, Armenia, August 29 - September 2, 2004 - NATO Advanced Research Workshop on Advanced Radiation Sources and Applications (NATO Science Series II: Mathematics, Physics and Chemistry,, 2006)
A NATO Advanced Research Workshop on ”Advanced Radiation Sources and Applications” was held from August 29 to September 2, 2004. Hosted by the Yerevan Physics Institute, Yerevan, Armenia, 30 invited researchers from former Soviet Union and NATO countries gathered at Nor-Hamberd, Yerevan, on the slopes of Mount Aragats to discuss recent theoretical as well as expe- mental developments on means of producing photons from mostly low energy electrons.